2021
DOI: 10.18203/2320-1770.ijrcog20211112
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anemia in pregnancy and its maternal-fetal outcome in admitted ANC patients in tertiary care center, Bhilai, Chhattisgarh, India

Abstract: Background: Anemia in pregnancy is an important public health problem in developing countries like India. Anemia results in poor pregnancy outcome and also affects fetal outcome. The present study was conducted to asses maternal and fetal outcome in relation anemia. Aim and objectives of the study was to determine incidence, risk factors and maternal-fetal outcome of anemia in the admitted pregnant women attending obstetrics and gyanecology department, shanakarcharya institute of medical sciences, Bhilai.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Researchers, in this case, have found out that the statistic of the study has more expressed microcytic anemia type over other types morphologically [8]. A study conducted in Chhattisgarh reported that in India as well as in developing countries fetal get this condition from low maternal incomes, and consumption of sufficient nutrients is supportively taken care of [12].It is important to note that the above discussion is based on the provided information and assumes that the study was conducted in a scientifically rigorous manner. To gain a comprehensive understanding of the study and its implications, it would be helpful to review the complete research findings, including methodology, statistical analysis, and limitations mentioned in the study.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Researchers, in this case, have found out that the statistic of the study has more expressed microcytic anemia type over other types morphologically [8]. A study conducted in Chhattisgarh reported that in India as well as in developing countries fetal get this condition from low maternal incomes, and consumption of sufficient nutrients is supportively taken care of [12].It is important to note that the above discussion is based on the provided information and assumes that the study was conducted in a scientifically rigorous manner. To gain a comprehensive understanding of the study and its implications, it would be helpful to review the complete research findings, including methodology, statistical analysis, and limitations mentioned in the study.…”
Section: Discussionmentioning
confidence: 85%
“…Additional tests were ordered by doctors on duty and mentioned on their medical files to evaluate serum ferritin levels, iron, total iron-binding, total iron binding capacity, and transferrin. [10][11][12][13][14][15] are represented by 14, 14, 13, 11, 8 and 3 participants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia during pregnancy is commonly associated with poor pregnancy outcome and may lead to complication of mother like Prolonged labour and increase incidence of postpartum haemorrhage and also lead to preterm birth, low birth weight and small-for-gestational age babies and prematurity. [10][11][12] Low haemoglobin levels in pregnancy has been seen to be associated with poor fetomaternal outcomes. [13,14] Oral iron has many side effects and is tolerated poorly, although it is the standard drug for the treatment of IDA in pregnancy.…”
Section: Discussionmentioning
confidence: 99%